Pleiotropic activity of antihypertensives in atherothrombogenesis. Nebivolol: increasing possibilities and reducing restrictions - M. G. Bubnova (Кардиоваскулярная терапия и профилактика, 2008)
The review is devoted to the recent European recommendations' view on antihypertensive medications (AHM). The role of beta-adrenoblockers (BAB) in treating arterial hypertension (AH) patients is emphasized. Existing differences in pharmacological parameters and clinical effects are discussed for BAB of various generations. Importance of AH patients' classification by total cardiovascular risk level is explained. The important role of additional (pleiotropic) AHM effects in atherothrombogenesis control is presented, with nebivolol as an example.